Epithelial cells fire voltage spikes - Sun-Min Yu; Steve Granick (Proceedings of the National Academy of Sciences, 2026)
Bioelectric signaling is well characterized in neurons and cardiomyocytes but remains largely unexplored in epithelia. Using multielectrode arrays, we demonstrate that localized laser injury to epithelial monolayers (primary human keratinocytes and MDCK cells) triggers voltage spikes in the range of 4 to 12 per min for over 60 min postinjury. These spikes exhibit depolarization, repolarization, and hyperpolarization phases lasting 1 to 2 s, a timescale three orders of magnitude slower than neuronal action potentials. Spike amplitudes and frequencies detected at 740 μm from the injury site (the maximum distance measured) are comparable to those at 140 μm and exhibit a nonmonotonic spatial profile, arguing against simple radial propagation from the wound. Calcium chelation with ethylenediaminetetraacetic acid abolishes spiking entirely, and inhibition of myosin II with blebbistatin produces equivalent suppression, indicating that calcium influx and actomyosin contractility are both required. The mechanosensitive channel modifier GsMTx4 partially suppresses spiking, implicating the role of stretch-activated ion channels. Most strikingly, pharmacological activation of the mechanosensitive channel TRPV4 and Piezo1 generates high-amplitude spikes (1 to 10 mV) even in the absence of injury, demonstrating that mechanosensitive channel activation is sufficient to drive epithelial electrical excitability. These findings reveal that epithelia, long thought to lack action-potential-like dynamics, possess intrinsic bioelectric excitability gated by mechanical stress, challenging the classical distinction that electrical signaling is exclusive to specialized tissues like neurons and muscles and suggesting a signaling modality for coordinating collective cellular responses across tissue-scale distances.